Intestinal stomas: A clinical study in a Teaching Hospital, our experience - Karki, Om Bahadur (Journal of Kathmandu Medical College, 2020)
Background: An intestinal stoma is an opening of the intestine on anterior abdominal wall made with an intention of either decompression of an obstructed colon or diversion of stool. Intestinal stomas may be temporary or permanent, depending on their role. Objectives: The objective of this study was to determine the common indications and types of intestinal stomas, and outcomes of patients operated at Manipal Teaching Hospital, Pokhara, Nepal. Methodology: A retrospective cross-sectional study was conducted in 105 patients of intestinal stomas from February 2017 to March 2020 in a teaching hospital after approval from institutional review committee. Data were derived from medical records of patients and operation logbooks with the consecutive sampling method. Data were analyzed with the help of the Statistical Package for Social Sciences (SPSS) version20 and p value < 0.05 was considered significant. Results: Total of 105 patients with intestinal stomas was included for the study of which 82.9% (n=63) were emergency operations and 17.1% (n=13) were elective. There were 46 (43.80%) cases of ileostomy, 9(8.5%) jejunostomy and 50(47.6%) colostomy patients. Major indications of stoma formation were trauma 33.3% (n=35) and intestinal obstruction 22.8% (n=24). Complications were observed in 39 (37.14%) of the patients, with wound infection 11.8% (n=9) and peristomal dermatitis 11.8% (n=9) for ostomates being the commonest. Higher complications were seen with ileostomy as compared to colostomy (p=0.02) and loop ileostomy still higher than end ileostomy (p=0.00). Conclusion: Common indications for intestinal stomas were abdominal trauma, enteric perforation, intestinal obstruction and colorectal carcinoma. Main complications included local skin problems, wound infection and retraction.